Ostre, idiopatyczne, obustronne zapalenie błony naczyniowej z towarzyszącym zapaleniem okołożylnym – opis przypadku - Nowosielska, Agnieszka; Czarnecki, Wojciech; Brydak-Godowska, Joanna; Dróbecka-Brydak, Ewa; Nowacka, Ewa; Lao, Mieczysław; Durlik, Magdalena (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The purpose of this paper is to present the case of 35 years old healthy male suffering from acute, bilateral uveitis with periphlebitis which despite broad ophthalmic and internal diagnosis remained of unknown origin. Despite anti-inflammatory treatment with acyclovir, ciprophloxacine and Encorton remission of inflammation was not achieved. Due to the failure of steroid treatment the decision of immunosuppressive therapy with Rapamycine and Endoxan was made. New therapeutic regimen caused the remission of inflammation and preserved patient’s useful visual acuity. Słowa kluczowe: zapalenie błony naczyniowej, zapalenie okołożylne, vasculitis, leczenie immunosupresyjne, Rapamycyna.d patient’s useful visual acuity.